Research on podocyte injury mechanisms in diabetic nephropathy: a bibliometric and knowledge-map analysis from 2000 to 2024 - Lin, Yanmei; Tian, Jianqing (Frontiers in Endocrinology, 2025)
ObjectivesA bibliometric and knowledge-map analysis is used to explore hotspots evolution and development trends in the Podocyte Injury Mechanisms in Diabetic Nephropathy. By looking for research hotspots and new topics, we can provide new clues and ideas for researchers in this field.MethodsThe articles and reviews regarding Podocyte were retrieved and obtained from the Web of Science Core Collection (WOSCC) on September 1st, 2024. CtieSpace [version 6.2.4R (64-bit)] and VOSviewer (version 1.6.18) were used to conduct the bibliometric and knowledge-map analysis.Results12086 authors from 2394 institutions in 69 countries/regions published 3239 papers in academic journals. PEOPLES R CHINA and THE USA were absolutely in the leading position in this research field. The institution that contributed the most publications was the Shandong University. Kidney International (130 articles) is the journal with the most published records and the highest number of co-citations. The author with the highest number of co citations is Mundel p. However, there was little cooperation between countries. After 2012, cooperation among various institutions was also small. Autophagy, mitochondria, and epigenetics are hot topics and trends in this field. The most influential research hotspots were the research of podocyte autophagy and metabolism, the related research of SIRT1, VEGF. The latest hotspots and topics included the study of nlrp3 inflammasome and signaling pathway in podocyte injury. The research of Podocyte in Diabetic Nephropathy was a rapidly developing hot field.ConclusionThe damage mechanism of podocytes is a very important factor in the occurrence and progress of diabetes nephropathy. Early intervention of podocyte damage is a very potential preventive measure for diabetes nephropathy, which has clinical application prospects and is currently being rapidly developed.